Monitoring Notch Signaling-Associated Activation of Stem Cell Niches within Injured Dental Pulp - Mitsiadis, Thimios A.; Catón, Javier; Pagella, Pierfrancesco; Orsini, Giovanna; Jimenez-Rojo, Lucia (Frontiers in Physiology, 2017)
Dental pulp stem/progenitor cells guarantee tooth homeostasis, repair and regeneration throughout life. The decision between renewal and differentiation of these cells is influenced by physical and molecular interactions with stromal cells and extracellular matrix molecules forming the specialized microenvironment of dental pulp stem cell niches. Here we study the activation of putative pulp niches after tooth injury through the upregulation of Notch signalling pathway. Notch1, Notch2 and Notch3 molecules were used as markers of dental pulp stem/progenitor cells. Upon dental injury, Notch1 and Notch3 are detected in cells related to vascular structures suggesting a role of these proteins in the activation of specific pulpal perivascular niches. In contrast, a population of Notch2-positive cells that are actively proliferative is observed in the apical part of the pulp. Kinetics of these cells is followed up with a lipophilic DiI labelling, showing that apical pulp cells migrate towards the injury site where dynamic regenerative/repair events occur. The knowledge of the activation and regulation of dental pulp stem/progenitor cells within their niches in pathologic conditions may be helpful for the realization of innovative dental treatments in the near future.